Plasma-enhanced atomic layer deposition of barium titanate with aluminum incorporation. (15th September 2016) - Kim, Yongmin; Schindler, Peter; Dadlani, Anup L.; Acharya, Shinjita; Provine, J.; An, Jihwan; Prinz, Fritz B.
Abstract: Plasma-enhanced atomic layer deposition (PEALD) of ultrathin (∼7 nm) slightly Ti-rich Bax Tiy Oz (BTO) films with different Al-doping concentration ([Al]/([Al] + [Ba] + [Ti]) = 0 to 22 at%) was studied. In particular, the effects of Al-doping in BTO on compositional, crystallographic and electrical properties were investigated. Previously, BTO films with a Ti cation composition, [Ti]/([Ba] + [Ti]) = ∼60 at% was reported to be advantageous for crystallization, resulting in superior dielectric properties. These Ti-rich BTO films, however, suffered from high leakage currents, necessitating the change in its crystalline structure as well as elemental composition. By incorporating Al2 O3 into the BTO films, the leakage current can be controlled, where the BTO films with an Al-doping concentration of 12 at% showed a leakage current reduced by one order of magnitude compared to un-doped BTO (i.e., ∼10 −7 to ∼10 −6  A/cm 2 at +1.6 V) without a significant drop of the dielectric constant (43, un-doped to 40, Al-doped). Graphical abstract: